A survey on the use of technology to support hospice interdisciplinary team meetings. (27th January 2009) - Demiris, George; Wittenberg-Lyles, Elaine; Oliver, Debra Parker; Courtney, Karen L.
Interdisciplinary teamwork is essential in the delivery of hospice services. Hospice agencies in the USA are required by law to follow an interdisciplinary approach to patient care. The goal of this study is to assess the current level of technology use in hospice Interdisciplinary Team (IDT) meetings and identify the areas where technology can be utilised to address the challenges or barriers that IDT meetings face. We conducted a semistructured phone survey using purposive sampling based on US hospice utilisation rates. The representatives of 190 agencies participated. The findings indicate that technology is not widely used in team meetings. Less than half of the agencies report computer use during meetings. The respondents saw benefits in using technology to access patient records and medication lists and design the care plan. Technology can become a powerful tool if introduced to enhance the social and product function of a group process.